2007
DOI: 10.1093/aob/mcm052
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Photosynthesis, Chlorophyll Fluorescence and ROS-Scavenging Systems to Salt Stress During Seedling and Reproductive Stages in Rice

Abstract: Upregulation of the anti-oxidant system appears to play a role in salt tolerance of rice, with tolerant genotypes also maintaining relatively higher photosynthetic function; during both the vegetative and reproductive stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
357
3
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 586 publications
(444 citation statements)
references
References 20 publications
39
357
3
9
Order By: Relevance
“…This is also related to ion accumulation at toxic levels in photosynthetically active leaf cells (Tester and Davenport 2003). A decline in P N as a consequence of NaCl toxicity has been reported by several authors in different rice cultivars (Abdullah et al 2001;Dionisio-Sese and Tobita 2000;Djanaguiraman et al 2006;Moradi and Ismail 2007;Pieters and Nuñez 2008;Walia et al 2005;Welfare et al 1996) as well as in other cereal crops such as sorghum (Netondo et al 2004), wheat (Sharma et al 2005;Zheng et al 2009) and naked oat (Zhao et al 2007). In accordance with this, we observed that P N of both cultivars declined significantly under 150 mM NaCl during the vegetative growth (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…This is also related to ion accumulation at toxic levels in photosynthetically active leaf cells (Tester and Davenport 2003). A decline in P N as a consequence of NaCl toxicity has been reported by several authors in different rice cultivars (Abdullah et al 2001;Dionisio-Sese and Tobita 2000;Djanaguiraman et al 2006;Moradi and Ismail 2007;Pieters and Nuñez 2008;Walia et al 2005;Welfare et al 1996) as well as in other cereal crops such as sorghum (Netondo et al 2004), wheat (Sharma et al 2005;Zheng et al 2009) and naked oat (Zhao et al 2007). In accordance with this, we observed that P N of both cultivars declined significantly under 150 mM NaCl during the vegetative growth (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Bomba and Bahia), i.e. the late vegetative growth and the reproductive stage, which has been shown to present different sensitivity to salt stress (Lutts et al 1995;Moradi and Ismail 2007;Rao et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leaves were transferred into the NBT solution for 3 h, boiled in 80% ethanol for 10 min, and stored in 100% ethanol. The H 2 O 2 and MDA contents and CAT activity were determined as described by Moradi and Ismail (2007).…”
Section: Tunel Assaysmentioning
confidence: 99%